TEACHER EVALUATION AND CURRICULUM RESEARCH AND DEVELOPMENT: IMPLICATION FOR INNOVATION AND PROFESSIONAL DEVELOPMENT. - Sujariati Sujariati; Yassir Mallapiang; Sufiana Sufiana (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2026)
This study aimed to examine how teacher evaluation interacts with curriculum research and development and to investigate the implications of this relationship for curriculum innovation and teacher professional development. Methodology used in this study was a qualitative research approach. Data were collected through three kinds of instruments namely semi-structured interviews with some teachers and two curriculum coordinators, analysis of curriculum innovation and evaluation documents, and teachers’ reflective notes. Dealing with data analysis, the data were analyzed through thematic steps to catch and capture patterns of interaction among teacher’s evaluation practices, curriculum research and development, and professional learning. The findings showed that teacher evaluation designed classroom-based insights that contributed to curriculum research and development with highlighted instructional teaching and learning practices, curriculum feasibility, and realistic condition of classroom challenges that were not fully represented in formal curriculum documents. Other findings were curriculum research and development gave influences to teacher evaluation by changing evaluation criteria became priorities toward student-centered learning and instructional innovation. However, alignment important points between evaluation criteria and new curriculum expectations were usually inconsistent and contrary with experience in practice. Evaluation feedback would be systematically connected to curriculum planning design and delivered relevant professional development and gave impact positively when teachers generated evaluation as supportive and conducive to professional growth. The study concluded that aligning teacher evaluation with curriculum research and development strengthened curriculum innovation and supported sustainable of teacher professional development. However, Hence, the findings served and provided evaluation to operate as capacity-building instrument that addressed to contextual classroom and fostered ongoing enhancement.